1994
DOI: 10.1002/pssa.2211450234
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Dependence of Hall Coefficient in Short-Period PbTe/SnTe Superlattices

Abstract: The dependence of the Hall coefficient on magnetic field (B < 1.5 T), measured at 77 K, in short‐period (D < 40 nm), strained PbTe superlattices is analysed and interpreted. It is concluded that the superlattice is of type II. In addition to the electrons in PbTe and holes in SnTe, a third kind of charge carriers, having a high mobility, appears to take part in the conduction process. The third carriers can be both electron and hole‐like particles. Those carriers are connected with interface states which are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…Mironov et al 3 have explained the anomalous behavior of the conductivity in their samples by a structural phase transition undergone by the SnTe layer. Litvinov et al 4 have used the presence of two-dimensional interface states to explain the magnetic field dependence of Hall coefficient of short-period SLs. Unfortunately, structural characterization of these samples has been almost forgotten, although many of the observed electrical properties and most of the open questions are probably related to structural details of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Mironov et al 3 have explained the anomalous behavior of the conductivity in their samples by a structural phase transition undergone by the SnTe layer. Litvinov et al 4 have used the presence of two-dimensional interface states to explain the magnetic field dependence of Hall coefficient of short-period SLs. Unfortunately, structural characterization of these samples has been almost forgotten, although many of the observed electrical properties and most of the open questions are probably related to structural details of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [8], it was concluded that in the PbTe/SnTe SLs, the hole concentrations in the SnTe layers were considerably smaller than those in the single films and bulk crystals of SnTe.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of two-dimensional states in the PbTe/SnTe interface was proved by experiment [1]. The electron-and hole-like particles associated with interface states exhibit a high mobility and lowered concentration compared with bulk carriers.…”
Section: Introductionmentioning
confidence: 93%